STUDI POTENSI TANAMAN BIOFARMACA DI KAWASAN IUPHKm “HANDAK MAJU” DESA TUMBANG NUSA, KECAMATAN JABIREN RAYA, KABUPATEN PULANG PISAU, PROVINSI KALIMANTAN TENGAH: Potential Study of Medicinal Plants in the IUPHKm “Handak Maju” Area at Tumbang Nusa Village, Jabiren Raya Sub-district, Pulang Pisau Regency, Central Kalimantan Province - Adji, Fengky Florante; Yulianti, Nina; Darung, Untung; Oemar, Oesin; Sustiyah, Sustiyah; Yosep, Yosep; Jemi, Renhart; S.A.H.AR, Putra; Segah, Hendrik; Meilantina, Meilantina; M.T, Munier; P, Talulembang (AgriPeat, 2023)
Peatland is a specific ecosystem that is always waterlogged and has multiple functions, including economic, hydrological, environmental, cultural, and biodiversity functions. Existing peatlands, especially in Central Kalimantan, have great biodiversity potential. This potential provides benefits for people living in peat areas. This diversity of biodiversity has the potential of medicinal plants that have not been maximally explored. Therefore, through this activity, data will be obtained regarding the types and potential of medicinal plants in inland peat areas, which will facilitate their management. This research activity was carried out in the “Handak Maju” IUPHKm area for 3 (three) months, from July – September 2022. The implementation method is carried out through survey activities and field observations and carrying out of the Focus Group Discussions, as well as related literature studies. Based on the results of the survey conducted, it was found that several types of medicinal plants have the potential to be developed and preserved. According to Zuhud (1991) that medicinal plants are plants whose plant parts (leaves, stems or roots) have medicinal properties and are used as raw materials in the manufacture of modern and traditional medicines. It was further revealed that, medicinal plants are still not widely cultivated. However, the advantages of treatment using traditional medicinal plant ingredients are generally considered safer than the use of modern medicine. This is because traditional medicine has relatively fewer side effects than modern medicine.